Effects of elevated temperature exposure on the microstructural evolution of Ni(Cr)-Cr3C2 coated 304 stainless steel - Ding, Yi (2009)
Agglomerated and sintered 25Ni(Cr)-75Cr3C2 powder was deposited onto 304 stainless steel substrates by HVOF thermal spraying. Post spraying thermal treatments were carried out on as-sprayed samples at different temperatures (700°C and 800°C) in air (oxidising). Samples were heat treated from 1hour up to 16 days and furnace cooled. The powder, coatings and substrate were characterised by a variety of techniques including optical microscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), microhardness testing and thermogravimetric analysis (TGA).